2011
DOI: 10.2118/131791-pa
|View full text |Cite
|
Sign up to set email alerts
|

Coalbed Methane: Current Field-Based Evaluation Methods

Abstract: Summary Coalbed methane (CBM) produced from subsurface coal deposits has been produced commercially for more than 30 years in North America, and relatively recently in Australia, China, and India. Historical challenges to predicting CBM-well performance and long-term production have included accurate estimation of gas in place (including quantification of in-situ sorbed gas storage); estimation of initial fluid saturations (in saturated reservoirs) and mobile water in place; estimation of the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 68 publications
0
44
0
Order By: Relevance
“…The prediction of permeability is economically crucial as it determines whether commercial gas production rates can be achieved. Gas stored in coal seams (Clarkson & Bustin 2011), as well as groundwater in the system is transported through the cleats towards the producing wells (Scott 2002). Because seam permeability is a crucial factor for mine stability, minability, gas well performance and drainage behaviour, knowledge of cleat characteristics is essential for safe and efficient mining.…”
Section: Relevance Of Cleat Geometry Measurementsmentioning
confidence: 99%
“…The prediction of permeability is economically crucial as it determines whether commercial gas production rates can be achieved. Gas stored in coal seams (Clarkson & Bustin 2011), as well as groundwater in the system is transported through the cleats towards the producing wells (Scott 2002). Because seam permeability is a crucial factor for mine stability, minability, gas well performance and drainage behaviour, knowledge of cleat characteristics is essential for safe and efficient mining.…”
Section: Relevance Of Cleat Geometry Measurementsmentioning
confidence: 99%
“…Historical challenges to predicting CBM-well performance and long-term production have included accurate estimation of gas in place (including quantification of in-situ sorbed gas storage); estimation of initial fluid saturations (in saturated reservoirs) and mobile water in place; estimation of the degree of under-saturation (under-saturated coals produce mainly water above desorption pressure); estimation of initial absolute permeability (system); estimation of absolute-permeability changes as a function of depletion; and accurate prediction of cavity or hydraulic-fracture properties (Clarkson & Bustin, 2010).…”
Section: Unconventional Gas Reservoir Uncertaintymentioning
confidence: 99%
“…The work by Clarkson & Bustin (2010) showed that there is difficulty in estimating original gas in place. This is partially due to the variability in coal seam thickness (Baker, et al, 2012;Kabir, et al, 2011) which is a key input to calculating the initial gas in place (Seidle, 2011).…”
Section: Unconventional Gas Reservoir Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Cleat system and production mechanism of CBM (King and Ertekin, 1989;Kansas Geological Survey, 2006). (Conway et al, 1994;Clarkson and Bustin, 2011 (Mavor and Saulsberry, 1996). …”
Section: Cbm 유정생산시험mentioning
confidence: 99%